A design and reconfigurable phase shift inductor inductor capacitor converter for switch failures - Xu Lili; Muhamed Nabil Hidayat; Nik Hakimi Bin Nik Ali; Muhammad Umair (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
The reliability of a converter operation strongly affects overall system performance and is vital for uninterrupted power-electronic operation. Harsh operating conditions and environmental stresses degrade device performance and reduce reliability. In particular, a switching device failure may prevent an inductor inductor capacitor (LLC) resonant converter from operating near its resonant frequency while still maintaining stable output voltage, potentially causing loss of operation as well as significant drops in both efficiency and power delivery. To address this challenge, this paper proposes a fault-tolerant topology and control strategy for the LLC converter under open circuit switch (OCF) faults. The proposed method integrates a bypass arm with a secondary-side series configuration; when a primary-side open-circuit fault occurs, the auxiliary switch is activated to bypass the faulty leg, reconfiguring the secondary side into a voltage doubler rectifier (VDR). This reconfiguration enables continuous operation with an output voltage doubled relative to the normal condition, while minimizing performance degradation. Simulation results confirm that, even under a single-switch OCF, the proposed approach maintains an efficiency of 98% with output voltage fluctuation limited to less than 1%. Compared to conventional methods, the proposed strategy greatly enhances reliability and fault tolerance, making it well-suited for high-efficiency power conversion applications.